Digital competency among students: a case study at UiTM Kelantan Branch / Nordelina Zulkarnain, Safawi Abdul Rahman and Muhammad Saiful Anuar Yusoff - Zulkarnain, Nordelina; Abdul Rahman, Safawi; Yusoff, Muhammad Saiful Anuar (Perpustakaan Tun Abdul Razak (PTAR), 2021)
IR4.0 technologies enable the learning to be conducted in an easier way and meaningful manner. Many online learning platforms such as Google Classrooms, Frog Classrooms and MOOCS are developed based on the IR4.0 technologies. Students should have necessary competencies in coping with IR4.0 learning technologies. However, there is a lack of digital skills among students as reported in the literature. This study investigates the level of digital competency among students in response to the prescribed issue. The samples were 389 students studying multiple academic programs in UiTM, Kelantan Branch. By adopting the questionnaires used in previous research, this study specifically measures the information and data literacy, communication, safety, digital content creation and problem-solving competencies following the DigComp Framework. The SPSS version 22 was employed for data analysis. The results indicate lowest score in digital content creations compared to other four competencies. The potential implication of this study is the emphasis on this competence as this skill requested is critical in digital gig economy.